Decision-Making Framework Using MARCOS for Evaluating Sealing Machines in Small and Medium Enterprises - Dewi, Marysca Shintya; Marlinda, Linda; Komarudin, Komarudin (Politeknik Ganesha Medan, 2025)
In the era of globalization, Micro, Small, and Medium Enterprises (MSMEs) hold a vital position in Indonesia's economy, contributing significantly to GDP and employment. Despite their importance, MSMEs need help in selecting appropriate sealer machines, which affects production efficiency and product quality. There are six different kinds of sealer machines that are looked at in this study. They are manual, vertical, continuous, horizontal semi-automatic, impulse, and vacuum. The MARCOS method is used to find the best option. Results indicate that the Impulse Sealer Machine (A5) is the most suitable, with a Ki value of 1.7, followed by the Continuous Sealer Machine (A3), with a Ki of 1.63. Machines such as Manual (A1), Vertical (A2), and Vacuum (A6) scored 1.6, while the Horizontal Semi-Automatic Sealer Machine (A4) ranked lowest at 1.36. These findings provide MSMEs with practical guidance for selecting sealer machines that enhance production efficiency and competitiveness in the global market while also contributing to the development of packaging technology research.